2007
DOI: 10.2214/ajr.05.2049
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of Pediatric Small-Bowel Intussusception: Differentiating Surgical from Nonsurgical Cases

Abstract: When small-bowel intussusception is detected in infants and children undergoing abdominal sonography, intussusception length greater than 3.5 cm is a strong independent predictor of the need for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 16 publications
6
59
1
9
Order By: Relevance
“…This information correlates with gravity and so with prognosis of intussusception, as also described by some Authors, for example by Munden et al that in their series found that length of intussusception was the most useful independent predictor of the need of surgical intervention and concluded that when small-bowel intussusception is detected in infants and children undergoing abdominal sonography, intussusception length greater than 3.5 cm is a strong independent predictor of the need of surgical intervention [19]. In the opinion of these Authors, transitory intussusception tends to have smaller both axial and longitudinal diameters compared to cases of nearly irreducible intussusception, in which diameters should be greater.…”
Section: Discussionsupporting
confidence: 55%
“…This information correlates with gravity and so with prognosis of intussusception, as also described by some Authors, for example by Munden et al that in their series found that length of intussusception was the most useful independent predictor of the need of surgical intervention and concluded that when small-bowel intussusception is detected in infants and children undergoing abdominal sonography, intussusception length greater than 3.5 cm is a strong independent predictor of the need of surgical intervention [19]. In the opinion of these Authors, transitory intussusception tends to have smaller both axial and longitudinal diameters compared to cases of nearly irreducible intussusception, in which diameters should be greater.…”
Section: Discussionsupporting
confidence: 55%
“…In a small study by Zhang et al, 15 outer ring thickness greater than 0.4 cm was predictive of need for surgical reduction; however no such relationship was found in similar studies. 13,16 Absence of color flow in Doppler suggests compromise of the mesenteric vasculature, indicating a potentially difficult reduction and a lower reduction success rate. 1,17,18 Characteristic US findings of the transient small bowel "ileal-ileal" intussusception include small size of the doughnut ring (2-3 cm), no recognizable lead point, short segment length of less than 3.5 cm, normal vascularity on color Doppler US, and preserved wall motion.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,18 Characteristic US findings of the transient small bowel "ileal-ileal" intussusception include small size of the doughnut ring (2-3 cm), no recognizable lead point, short segment length of less than 3.5 cm, normal vascularity on color Doppler US, and preserved wall motion. 1,4,13,16,17,[19][20][21] Due to the availability of US imaging in most emergency departments, small bowel intussusceptions may be readily identified and characterized by these recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel intussusceptions have very little fat centrally and occur in older children with bowel disorders such as HenochSchonlein Purpura, Crohn disease, and celiac sprue; they are also seen in post-operative patients and in patients with small bowel mass acting as a lead point. Small bowel intussusception length greater than 3.5 cm is a strong predictor of need for surgical intervention [30] . However, most small bowel intussusceptions are idiopathic and transient [31] .…”
Section: Acquired Disordersmentioning
confidence: 99%